Advances in the Cognitive Management of Chronic Pain in Children through the Use of Virtual Reality Combined with Binaural Beats: A Pilot Study. (31st December 2022) - Riera, Laia; Verger, Sebastià; Montoya, Pedro J.; Perales, Francisco J.
Abstract : Chronic pain affects the quality of life of those affected. The need to investigate alternative and complementary methods to the pharmacological one to alleviate chronic pain is evident, so virtual reality and binaural tones have become a topic of interest in this field in recent years. This study aims to analyze the contributions of the combination of these two techniques in pediatric patients with chronic pain. For this, data on psychophysiological responses (heart rate and galvanic skin response) and pain perception are collected during and after interaction with this technology using a mixed pre- and posttest experimental methodology. The physiological data and answers in the Pediatric Pain Questionnaire (PPQ) have been collected in a sample of n  = 13 healthy participants and n  = 9 pediatric patients with chronic pain. The results show a significant difference between baseline and after applying virtual reality and binaural beats, m d  = 1.205 ( t  = 3.32; p < 0.05 ). There are great effects on the perception of chronic pain if virtual reality and binaural beats are combined, even greater than with virtual reality alone, making this combination of technologies a very useful tool to be exploited for the management of chronic pain in pediatric patients with rheumatic diseases.